Maternal attitudes and child mental health across cultures: a European /Chinese comparison - Kovess-Masfety, Viviane; Touma, Nathalie; Yan, Guoli; Yin, Huifang; Gölitz, Dietmar; Bitfoi, Adina; Lesinskiene, Sigita; Mihova, Zlatka; Otten, Roy; Xu, Guangming (European Child & Adolescent Psychiatry, 2025)
This study sought to identify factors associated with parenting across Western Europe, Eastern Europe and China countries, and determine whether the associations between parental attitudes and child’s mental health differ across countries. This cross-sectional study included mothers and their children. European data were drawn from the School Child Mental Health in Europe study, conducted in the Netherlands, Germany, Lithuania, Bulgaria and Romania, including 4104 dyads. Chinese data were collected from the Dongli District of Tianjin, including 1000 dyads. Parental attitudes were auto reported using Parenting Scale and Parent Behavior and Attitude Questionnaire. Children’s mental health was auto reported using the Dominic Interactive. Parenting vary across cultures and impact children’s mental health differently. Whatever the parental attitudes, the main determinants were related to family configuration, parental well-being and place of residence. Some associations were culture-specific: parent’s distress associated with laxness, over-reactivity and low autonomy-promoting attitudes in Europe. Single parenting correlated with low autonomy-promoting attitudes in China but low caring in Western Europe. Urban parents exhibited less laxness and low caring in Eastern Europe. The impact on children’s mental health also varied: over-reactivity was linked to internalized and externalized disorders in Western Europe, verbosity associated with internalized and externalized disorders in China, and low caring was linked to externalized disorders in Eastern Europe. Parental diverse attitudes are associated with different children mental health problems; these associations are not identical in the different regions emphasizing the need to tailor existing supporting parental interventions with a culturally sensitive approach.
CRIS-Team Scopus Importer:2025-04-04
Keywords: Children; China; Cross-cultural study; Europe; Mental health; Parental attitudes